Can you be both a conservative and a liberal? Frank Meyer and “fusionism” - Saar, Marcin (Hybris, 2019)
The topic of this paper is the thought of Frank S. Meyer, a prominent figure in post-world-war-II american right-wing intellectual movement. One feature commonly ascribed to Meyer is the ambition to fuse (thus the term “fusionism” assossiated with his name) a classical liberal concern for individual freedom and more conservative persuasion of virtue being the ultimate goal of human existence. With the issue of right relation of freedom to virtue are grouped other issues, also meriting consideration: the problem of use of reason and tradition in political enquiry, the nature and proper role of the state, the relation of individual person to society (or other superindividual entities). We look at these issues throughout this paper. We look also at Meyer’s position in intellectual traditions of liberalism (broadly construed) and conservatism, concluding that he belongs to the liberal camp (classical liberal, more on the libertarian side), and not to the conservative one.